Juvenile nulliparous uterine prolapse in an unmarried 17-year-old adolescent (Nepal Journal of Obstetrics and Gynaecology, 2022)
In a peripheral health camp, a 17-year-old juvenile nullipara who presented with the history of something coming out per vagina was clinically diagnosed as third-degree pelvic organ prolapse (POP) Stage III, acknowledged as a rarity concerning patient wellbeing and reproductive future.